Contests for Cooperation: A New Approach in German Innovation Policy - Alexander Eickelpasch; Michael Fritsch (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2005)
A new approach in German innovation policy organizes contests of proposals for developing innovation networks. Based on an overview of the different programs, we investigate the advantages, problems and limitations of such an approach. We find that this type of policy may have a relatively large impact and can, therefore, be regarded as a rather efficient instrument of innovation policy. Compared to conventional policies, administration of the program is a much more critical issue. The contest approach may stimulate learning effects on the side of the administration but may also require a high degree of flexibility. The main disadvantage is the additional time that is required for conducting the contest. As a distinct "picking the winner" approach, the contest approach is not suited as a means for achieving a leveling-out of regional welfare levels. – – In einem neuen Ansatz der deutschen Innovationspolitik werden Wettbewerbe für Vorschläge zur Entwicklung von Innovationsnetzwerken organisiert. Ausgehend von einem Überblick über diese Programme diskutieren wir Vorteile, Nachteile und Grenzen dieses Ansatzes. Es zeigt sich, dass diese Art der Innovationsförderung große Wirkungen erzeugen kann und daher vermutlich effizienter ist, als andere Typen von Programmen. Im Vergleich zu konventionellen Formen der Innovationsförderung ist allerdings die Administration des Programms sehr viel anspruchsvoller. Der Wettbewerbs-Ansatz kann Lerneffekte der Administration stimulieren aber auch ein relativ hohes Maß an Flexibilität erfordern. Der wesentliche Nachteil ist die zusätzliche Zeit, die für die Durchführung des Wettbewerbs benötigt wird. Da ein Wettbewerb ein ausgesprochenes ?Pick the Winner?-Vefahren darstellt, ist dieser Ansatz für eine ausgleichsorientierte Regionalpolitik kaum geeignet.
Keywords: O38; O18; H32; R11; 330; Innovationspolitik; Wettbewerb zwischen Regionen; Innovationsnetzwerke; Innovation policy; regional competition; innovation networks; Industriepolitik; Innovationspolitik; Innovationswettbewerb; Business Network; Deutschland